PENYUTRADARAAN FILM FIKSI KARSA MELALUI PENDEKATAN REALISME SEBAGAI PENGUATAN KARAKTER TOKOH - Dimas Fikri Aliyana; Citra Dewi Utami (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2023)
Death is a sure thing to happen. Death became an idea to take advantage of the rest of life by planning, striving, and trying. The purpose of this creation is to how Karsa's film is directed by applying an approach to realism as a reinforcement of the character's character. The realism approach in this film is an attempt to present a story that is as simple and close to reality as possible. The character in the film has a very important role because the character is one of the points that an audience pays attention to. A strong character will make a good impression on a movie. The result of this film is how the realism approach with long take and deep focus shooting techniques can strengthen the character's character through the process of reading, rehearsal, dialogue, and small discussions between the director and the performer. The message to be conveyed to the audience is that death is always close to us and death needs to be prepared. The conclusion of strengthening the Raka character is that it consists of the character of his independence and laziness. Meanwhile, the strengthening of Sarah's character consists of a character who is full of effort, emotion, and illness.